(untitled) (ENTHYMEMA, 2018)
Il saggio si propone di esplorare il volume Ex.it apparso nel 2013 che presenta tra alcune delle più significative scritture di ricerca italiana contemporanea. In particolare, s’intende analizzare il territorio della cosiddetta prosa in prosa, cercando di capirne le matrici e gli sviluppi. S’individuano al contempo alcuni principi fondamentali che possono aiutarci ad orientarci nei testi in questione, ovvero la matericità, la spazialità e la visività. Questi stessi principi mostrano il profondo dialogo che tali scritture hanno con le arti visive. The essay aims to explore the volume Ex.it appeared in 2013 that presents some of the most significant Italian contemporary research writings. In particular, we intend to analyze the territory of the so-called prose in prose, trying to understand its matrixes and developments. At the same time, we identify some fundamental principles that can help us to orient ourselves in the texts in question, that is the materiality, the spatiality and the visual. These same principles show the profound dialogue these writings have with the visual arts.